2011
DOI: 10.1016/j.engstruct.2011.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of the seismic performance of steel MRFs with compressed elastomer dampers using large-scale real-time hybrid simulation

Abstract: Real-time hybrid simulation combines experimental testing and numerical simulation, and thus is a viable experimental technique for evaluating the effectiveness of supplemental damping devices for seismic hazard mitigation. This paper presents an experimental program based on the use of the real-time hybrid simulation method to verify the performance-based seismic design of a two story, four-bay steel moment resisting frame (MRF) equipped with compressed elastomer dampers. The laboratory specimens, referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…Lin and Chopra [14] showed that brace flexibility has negligible effect on the peak responses of elastic systems for practical applications where braces are designed to have stiffness more than 5 times larger than the story stiffness (e.g., design cases of steel MRFs with dampers in [22][23]). …”
Section: Simplified Nonlinear Structural Systems With Viscous Dampersmentioning
confidence: 99%
See 2 more Smart Citations
“…Lin and Chopra [14] showed that brace flexibility has negligible effect on the peak responses of elastic systems for practical applications where braces are designed to have stiffness more than 5 times larger than the story stiffness (e.g., design cases of steel MRFs with dampers in [22][23]). …”
Section: Simplified Nonlinear Structural Systems With Viscous Dampersmentioning
confidence: 99%
“…Dampers are placed between successive floors of a building by using supporting braces which are designed to be stiff enough so that story drift produces damper deformation rather than brace deformation [22][23]. Lin and Chopra [14] showed that brace flexibility has negligible effect on the peak responses of elastic systems for practical applications where braces are designed to have stiffness more than 5 times larger than the story stiffness (e.g., design cases of steel MRFs with dampers in [22][23]).…”
Section: Simplified Nonlinear Structural Systems With Viscous Dampersmentioning
confidence: 99%
See 1 more Smart Citation
“…Steel moment-resisting frames (MRFs) equipped with passive dampers are another class of resilient structures. Previous analytical and experimental research showed that steel MRFs with passive dampers can be designed to be lighter and perform better than conventional steel MRFs under the design basis earthquake (DBE) and the maximum considered earthquake (MCE) [26][27]. A study shows that supplemental viscous damping does not always ensure adequate reduction of RDs [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analytical and experimental research showed that steel MRFs with passive dampers can be designed to be lighter and perform better than conventional steel MRFs under the design basis earthquake (DBE) and the maximum considered earthquake (MCE) [26][27]. A study shows that supplemental viscous damping does not always ensure adequate reduction of RDs [26][27][28]. A recent work evaluates the seismic collapse resistance of steel MRFs with linear viscous dampers and shows that supplemental viscous damping does not always guarantee a better seismic collapse resistance when the strength of the steel MRF with dampers is lower or equal to 75% of the strength of a conventional steel MRF [29].…”
Section: Introductionmentioning
confidence: 99%